Outcomes of Accelerated Physical Therapy in Patients with Transtendinous Rotator Cuff Repair (234). Issue 10 (31st October 2021) - McBroom, Trevor; Abraham, Paul; Varady, Nathan; Kucharik, Michael; O'Donnell, Evan; Martin, Scott
Objectives: Surgical treatment options for the repair of symptomatic partial thickness and minimally retracted full-thickness rotator cuff tears include transtendinous or tear-completion transosseous-equivalent approaches. While transtendinous repairs are associated with superior biomechanical outcomes and lower rates of cuff re-tear, they have been linked to greater stiffness and a slower rate of recovery in comparison to tear-completion transosseous-equivalent repairs, especially in the first three months postoperatively. The purpose of this retrospective matched cohort study was to examine whether expediting a patient's physical therapy (PT) regimen immediately following transtendinous rotator cuff repair can avert complications of postoperative stiffness and improve range of motion. Methods: After institutional review board approval, the medical records of all patients who underwent arthroscopic rotator cuff repair by the senior author between March of 2015 and May of 2019 were reviewed for inclusion in the study. Inclusion criterion was transtendinous repair. Patients that underwent an accelerated PT regimen were compared to a historical control cohort. The accelerated rehabilitation cohort was allowed passive range of motion (PROM) at 2-4 weeks, active-assisted range of motion (AAROM) at 2-4 weeks, active range of motion (AROM) at 4-6 weeks and strengthening exercises at 6-8 weeks. The historical control cohort received transtendinous rotator cuff repair between February 2005 and February 2015, and subsequently underwent a standard postoperative protocol with no shoulder motion until 6 weeks, PROM at 6-12 weeks, and AROM and strengthening exercises at 3-6 months. These cohorts were propensity matched for age, sex, BMI, and smoking status (with exact matches for sex and smoking status). Medical charts were reviewed for arthroscopic findings, including the tendons repaired (supraspinatus, infraspinatus, subscapularis, or a combination), arthroscopic classification of the tear thickness (partial, high-grade partial, focal full, or full), and presence of a concurrent labral tear. Patient data were analyzed with a mixed effects model to evaluate differences in active ROM at 2 weeks, 6 weeks, 3 months, and 6 months postoperatively. Forward flexion, abduction, and external rotation were recorded in degrees. Internal rotation was converted from vertebral levels to the Constant Shoulder Score's numerical ten-point scale for analysis. Finally, re-tear complications were recorded at final follow-up of 6 months and then analyzed with Fisher's exact test. Results: Sixty-one accelerated PT patients and 61 standard PT controls were included in the study. Mean age (57.02 ±2.70 years [95% confidence interval] vs. 57.45 ± 2.78 years, p=0.83), BMI (28.13 ± 1.13 kg/m 2 vs. 28.28 ± 0.99 kg/m 2, p=0.84), sex (61.66% female vs. 61.66% female p=1.00), and smoking status (p=1.00) were similar between groups. There were no significant differences between groups in the tendons repaired, the arthroscopic tear thickness, nor the presence of labral tears. (Table 1). The accelerated PT cohort showed significantly increased AROM at 6 weeks and 3 months postoperatively. At 6 weeks, ROM in forward flexion (136.97° vs. 110.52°; p<0.001), abduction (126.08° vs. 100.73°; p=0.003), and external rotation (51.65° vs. 37.90°; p=0.009) were all significantly higher in the accelerated PT cohort. A similar increase was seen at 3 months, with superior forward flexion (147.47° vs. 132.84°; p=0.009), abduction (140.44° vs. 121.91°; p=0.02), and external rotation (57.70° vs. 40.76°; p=0.001) in patients who received accelerated PT. With the exception of forward flexion, which was improved in the accelerated cohort (151.32° vs. 139.11°; p=0.04), there were no other differences in active ROM at 6 months. Internal rotation metrics approached statistical significance at 2 and 6 weeks postoperatively (p=0.07 and p=0.06, respectively). There were no re-tears (0.00%) in the accelerated PT cohort and 1 re-tear (1.64%) in the standard PT cohort (p=1.00). (Table 2). Conclusions: Accelerated PT following transtendinous rotator cuff repair is associated with substantial improvement in AROM at 6 weeks and 3 months when compared to standard PT protocols. Further, the early motion does not seem to result in a higher rotator cuff re-tear rate. Thus, early motion and liberation from obligate sling wear may reduce stiffness and be better tolerated following transtendinous rotator cuff repair surgery.